1987
DOI: 10.1172/jci112914
|View full text |Cite
|
Sign up to set email alerts
|

Apical membrane chloride/base exchange in the rat proximal convoluted tubule.

Abstract: To examine whether Cl/base exchange is present on the apical membrane of the proximal convoluted tubule, cell pH was measured fluorometrically in the in vivo microperfused rat proximal tubule with (2',7')-bis(carboxyethyl)-(5,6)-carboxyfluorescein.The effect of luminal chloride addition was examined in tubules perfused symmetrically with chloride-free solutions. In the absence of inhibitors, luminal chloride addition did not affect cell pH. However, after inhibition of basolateral membrane anion transport with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

1989
1989
2015
2015

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 32 publications
0
29
1
Order By: Relevance
“…superficial S2 proximal tubule is mediated by an apical Na+/ H+ exchanger in parallel with a C1-/OH-exchanger and that the secreted H + and OH -ions form H20 in the tubule lumen. Previous studies have failed to measure appreciable apical Cl -/base exchange in the intact tubule using cell pH measurements in the absence of exogenous formate (26,27). Several factors and methodological differences distinguish the studies of Alpern (26) and Baum (27) from the present study and may account for the marked Cl--induced changes in pHi observed.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…superficial S2 proximal tubule is mediated by an apical Na+/ H+ exchanger in parallel with a C1-/OH-exchanger and that the secreted H + and OH -ions form H20 in the tubule lumen. Previous studies have failed to measure appreciable apical Cl -/base exchange in the intact tubule using cell pH measurements in the absence of exogenous formate (26,27). Several factors and methodological differences distinguish the studies of Alpern (26) and Baum (27) from the present study and may account for the marked Cl--induced changes in pHi observed.…”
Section: Discussionmentioning
confidence: 54%
“…After luminal Cl -removal (solution B), pHi increased by only 0.04 pH units with an EBF of 2.76 pmol/min per mm (Table II). To enhance the measured effect on EBF induced by luminal Cl-removal, an attempt was made to inhibit Na+-dependent transport processes as previously described (26,27). S2 tubules were perfused with 2 mM luminal amiloride and 1 mM basolateral H2DIDS.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the proximal tubule of the rabbit, rat, and mouse kidney, the addition of low concentrations of formate to the luminal and peritubular solutions increased the rate of NaCl absorption (1,2). The formate-stimulated NaCl absorption was electroneutral and inhibited in the presence of DIDS (1-3, 5, 39, 44).…”
Section: /Hmentioning
confidence: 99%